Game Edukasi Museum Adityawarman Berbasis Android - Robby Usman (Majalah Ilmiah UPI YPTK, 2020)
Museum is a vehicle that has a strategic role in strengthening people's identity. One of the museums that exhibits historical relics is the State Museum of West Sumatra Province, known as the Adityarwan Museum. The Adityawarman Museum is the most important cultural museum in West Sumatra. The museum functions as a place to store and preserve historical objects, such as: Minangkabau cultural heritage, Mentawai cultural heritage and other archipelago cultural heritage. The use of smartphones, iPads, playbooks, tablet PCs and the like is more widely used today for various reasons and choices than PCs (Personal Computers) at home. In addition, there are many game features that are not only for entertainment, but there are already many games to hone thinking and logic that can educate children. Android is an operating system for Linux-based mobile devices which includes an operating system, middleware, and applications. Android provides an open platform for developers to create their applications. Android is the operating system that powers more than a billion smartphones and tablets